1997
DOI: 10.1046/j.1365-3059.1997.d01-220.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of bergenin, a constituent of Flueggea microcarpa

Abstract: The antifungal activity of bergenin against some plant pathogenic fungi, namely, Alternaria alternata, A. brassicae, A. carthami, Fusarium udum, F. oxysporum f.sp. ciceri, Curvularia lunata and Erysiphe pisi, was studied. Bergenin as its monosodium salt was effective against all the fungi and the effective dose for complete inhibition of spore germination varied from 15 mg mL ¹1 for F. udum to 125 mg mL ¹1 for E. pisi. Experiments on the effect of bergenin on powdery mildew development under glasshouse conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 11 publications
0
22
0
2
Order By: Relevance
“…Miconazole had MIC of 0.293,0.146 and 0.146 µM,respectively for A. flavus,A. niger,and A. nidulans,whereas bergenin had MIC of 1,093.0,476.1,951.9 µM. No previous studies of bergenin were reported, except against plant pathogenic fungi, where difficulties of adsorption of bergenin in the plant tissues were found (Prithiviraj et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Miconazole had MIC of 0.293,0.146 and 0.146 µM,respectively for A. flavus,A. niger,and A. nidulans,whereas bergenin had MIC of 1,093.0,476.1,951.9 µM. No previous studies of bergenin were reported, except against plant pathogenic fungi, where difficulties of adsorption of bergenin in the plant tissues were found (Prithiviraj et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action of bergenin is not known (Prithiviraj et al, 1997). Many phenol compounds isolated from plants show antifungal activity, including some gallic acid derivatives (Maillard et al, 1987;Singh et al, 1988;Da Silva et al, 2008) and bergenin is likely to act as these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Bergenin has been reported to have several biological activities, such as anti-inflammatory, 10,11 antioxidant, 12 hepatoprotective, 13 neuroprotective, 14 anti-HIV 15 and antifungal. 16,17 Here we report antiinflammatory activity of bergenin and the quantification of bergenin in an aqueous extract of bark, prepared as prescribed in the traditional medicine, by RP-HPLC. The inhibitory activity of bergenin against important enzymes (phospholipase A 2 and cyclooxygenases) involved in inflammatory mechanisms was also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the rate of cytotoxicity depends on the presence and position of hydroxyl group in the isocoumarin framework. 37 Thunberginol B 22a-22b, naturally occurring isocoumarins, also show anticancer effect ( Figure 5). In addition, thunberginol B has been found to have antiallergic, antimicrobial, antioxidant, and choragic activities.…”
Section: −30mentioning
confidence: 99%